Multiparametric CMR imaging of infarct remodeling in a percutaneous reperfused Yucatan mini‐pig model. (6th February 2017) - Lopez, David; Pan, Jonathan A.; Pollak, Peter M.; Clarke, Samantha; Kramer, Christopher M.; Yeager, Mark; Salerno, Michael
Abstract : To further understanding of the temporal evolution and pathophysiology of adverse ventricular remodeling over the first 60 days following a myocardial infarction (MI) in both the infarcted and remote myocardium, we performed multi‐parametric cardiac magnetic resonance (CMR) imaging in a closed‐chest chronic Yucatan mini‐pig model of reperfused MI. Ten animals underwent 90 min left anterior descending artery occlusion and reperfusion. Three animals served as controls. Multiparametric CMR (1.5T) was performed at baseline, Day 2, Day 30 and in four animals on Day 60 after MI. Left ventricular (LV) volumes and infarct size were measured. T 1 and T 2 mapping sequences were performed to measure values in the infarct and remote regions. Remote region collagen fractions were compared between infarcted animals and controls. Procedure success was 80%. The model created large infarcts (28 ± 5% of LV mass on Day 2), which led to significant adverse myocardial remodeling that stabilized beyond 30 days. Native T 1 values did not reliably differentiate remote and infarct regions acutely. There was no evidence of remote fibrosis as indicated by partition coefficient and collagen fraction analyses. The infarct T 2 values remained elevated up to 60 days after MI. Multiparametric CMR in this model showed significant adverse ventricular remodeling 30 days after MI similar to that seen in humans. In addition, this study demonstrated that remote fibrosis is absent and that infarct T 2 signal remains chronically elevated in this model. These findings need to be considered when designing preclinical trials using CMR endpoints. Abstract : Multiparametric CMR images were obtained from a closed‐chest chronic Yucatan mini‐pig model of reperfused myocardial infarction at different time points. Acutely there is increased wall thickness at the infarct region (arrows) followed by wall thinning (arrow heads) and ventricular remodeling at later time points. Notably, T 2 signal remains elevated throughout the study period and the acute infarct region is not readily identified on native T 1 imaging (T1 Pre).